Intruders/ Short stories - Mashigo, Mohale, 1983- (Johannesburg, South Africa: Picador Africa, 2018)
Orphan sisters chase monsters of urban legend in Bloemfontein. At a busy taxi rank, a woman kills a man with her shoe. A genomicist is accused of playing God when she creates a fatherless child. Intruders is a collection that explores how it feels not to belong. These are stories of unremarkable people thrust into extraordinary situations by events beyond their control.
Adult